O registro de marca e trade dress como diferencial competitivo : o caso do restaurante Gabi Comida Moda Caseira - Saraiva, Tennessee Lucena (2019)
Any business segment is fully competitive, but not always loyal. This causes companies to claim their rights for unfair competition. In order to preserve its image before its customers and related consumers. The family-owned company Gabi restaurant fruit of this research applied for its trademark application before the National Institute of Industrial Property - INPI. Because you realize that there is a risk that your brand such as trade dress can be used by third parties without prior authorization, and can generate a series of negativeconsequences both economic and reliable. Bringing the issue of unfairness to the agenda, this dissertation aims to demonstrate that trademark complement with trade dress have important potential of distinctiveness that promotes difficulty to unfair competition through judicial issues. Giving the brand a unique layout demonstrates extraordinary characteristics that can point to product or service differences, making it unfair to plagiarize, but making it easier for consumers to make a decision when buying. The methodology performed in this study includes visits to the company Gabi restaurant, were also conducted qualitative research at exploratory level, consisting of literature reviews and understanding of the concepts of own brand identity covered by trade dress. For all that was researched about the potentialities of intellectual property in conjunction with the trade dress, are presented several concepts that make up the competitive differential by the company that adopts Industrial Property - PI, as a business advantage over the others, and when the owner of the original. is disrespected must seek justice as a means of defense. The results show that when the trademark and trade dress are aligned, there is the use of the legal alliance that protects the registration with the INPI, in accordance with current legislation, having the trademark in question a competitive trait. Thus, it is concluded that, although there is no specific legislation on trade dress, there are several jurisprudences that ensure the protection of this characteristic element in this way, being possible to decide cases of judicial claim between original and fraudulent trademarks.